Katalog : Ervervelser 2003-2005. (Oslo : National Museum of Art, Architecture and Design Oslo, 2006)
Aarnio, Eero ; Afdal, Torbjorn ; Agnoli, Tito ; Antonsen, Gunvor Nervold ; Arad, Ron ; Arneberg, Arnstein ; Asbjornsen, Svein ; Aunaas, Henrikke ; Aune, Arnfinn Gunnar ; Baade, Knud Andreassen ; Bakke, Gunnhild ; Bakke, Ingunn ; Balenciaga, Cristobal ; Bang & Olufsen ; Bang, Nina ; Barbo, Vibeke ; Batchelor, Badi ; Becher, Bernd & Hilla ; Behrens, Millie ; Behrens, Peter ; Bellini, Mario ; Benson, William Arthur Smith ; Berg, Gerhard ; Berg, Sigrun ; Bergman, Anna-Eva ; Bergslien, Knud ; Bernadotte, Sigvard ; Berntsen, Sofie ; Best, Robert ; Bjorg, Toril ; Bjorlo, Per Inge ; Bjorneboe, Bjorn ; Blavarp, Liv ; Bloch, Andreas ; Bogler, Theodor ; Bohn, Ingun Erlandsen ; Boman, Axel Enoch ; Bonatti, Silvio ; Bongard, Hermann ; Bonsach, Baard ; Borgenhov, Aleksander ; Brandt, Marianne ; Brantenberg, Ulla-Marie ; Bratteli, Marianne ; Breivik, Bard ; Bring, Ebba ; Brochmann, Karen Berner ; Brochmann, Odd ; Bye, Bjorn ; Bye, Roar Matheson ; Calder, David ; Carick, V. ; Carlsen, Bjorn ; Charalas ; Chauton, Ulla ; Chernysheva, Olga ; Chihuly, Dale ; Coderock og K8 industridesign ; Dahl, Birger ; Dahl, Johan Christian ; Dean, Tacita ; Dhunsi, Nirmal Singh ; Disen, Ida ; Ditzel, Nanna ; Dokken, Siri ; Dolven, A.K. ; Dorwin Teague, Walter ; Dragset, Ingar ; Eckhoff, Sigrid ; Eckhoff, Tias ; Egorova, Olga ; Eide, Geir ; Einarsson, Gardar Eide ; Ekwall, Axel ; Eldoy, Olav ; Elmgreen, Michael ; Elvestuen, Per ; Ender, Axel ; Engebret, Bjarne ; Engo, Bjorn ; Erichsen, Agnete ; Evensen, Kristin ; Fabritius og Sonner ; Faldbakken, Matias ; Federspiel, Carla ; Feyling, Thorbjorn ; Fido industridesign AS ; Finseth, Ove Harder ; Fisker, Kay ; Fjeldsaa, Kare Berven ; Fjerdingstad, Christian ; Flatheim, Steinar ; Flor, Elinor ; Flygenring, Hans ; Formel Industridesign AS ; etc.
Noors
Exhibition. Coming together. New acquisitions 2003-2006. National Museum of Art, Architecture and Design Oslo, 02.09.2006 - 21.01.2007.
boek
Keywords: Noorwegen